The Pittsburgh school of philosophy : Sellars, McDowell, Brandom - Maher, Chauncey, 1979- (Routledge studies in contemporary philosophy ;, 2012)
In this volume, Maher contextualizes the work of a group of contemporary analytic philosophers-The Pittsburgh School-whose work is characterized by an interest in the history of philosophy and a commitment to normative functionalism, or the insight that to identify something as a manifestation of conceptual capacities is to place it in a space of norms. Wilfrid Sellars claimed that humans are distinctive because they occupy a norm-governed "space of reasons." Along with Sellars, Robert Brandom and John McDowell have tried to work out the implications of that idea for understanding knowledge, thought, norms, language, and intentional action. The aim of this book is to introduce their shared views on those topics, while also charting a few key disputes between them